Space and Place – Reflections in the Context of Inclusive Education - Iwona Chrzanowska (Studia z Teorii Wychowania, 2025)
The concept of space and place is currently experiencing a renaissance in the discourse of social sciences and humanities. Their understanding, interdependence, and significance for the processes of individual and social (group) development of students—particularly within the social and cultural dimensions of space—appear crucial in planning changes to the educational space of inclusive schools.The premise of inclusive education is to provide the highest quality education for all students. This indirectly implies that many aspects of schools must change since their existing structure has not facilitated this goal. Schools must change not only because they include students with disabilities, for instance, but because their current form is inadequate for any student.Hence, this proposal calls for reflection and literary analyses that incorporate understandings of the concepts of space and place drawn from philosophy, sociology, and pedagogy to provide arguments for what and why changes are necessary, how to identify patterns, and how to respond to them. The text emphasizes the social dimension of space, its relational nature, and its perception as a "nurturing place”, or space understood as a framework for building a community where everyone belongs and contributes.The context of inclusive education in considerations of space and place also invites reflection on the purist perception of individualization in working with students (especially those with disabilities or developmental disorders) as a prerequisite for the success of all initiatives. Can such an approach enable the creation of a shared space, and what role will the student play in this process?